Efektivitas Penerapan E-Government di Kabupaten Mamuju Provinsi Sulawesi Barat - Zainuddin, Muhlis (Gorontalo Journal of Government and Political Studies, 2019)
Information and Communication Technology has become a basic need in people's lives and services by the government. The government as the executor of public services uses eGovernment as a means and infrastructure to realize effective, efficient and accountable. The application of e-Government in each district / city has a different level of effectiveness, so research needs to be done to improve and determine the future direction. This research was conducted in Mamuju District, West Sulawesi Province. This research approach is descriptive by using a type of qualitative research that aims to analyze the results of data processing based on theoretical indicators. Data collection techniques are carried out by in-depth interviews, observations, and documentation studies. Data analysis techniques with data reduction, data presentation and conclusion / verification with triangulation theory, which underlies the theory of The Four Forces Model of e-Government, research in the field, and data analysis to draw conclusions. The results showed that the implementation of e-Government in Mamuju District was not yet effective. Of the twelve indicators only four indicators are met. Not Achieving Effectiveness The application of e-Government in Mamuju Regency is caused by a lack of understanding of e- Government at the executive level, regional officials, technical officials, and legislative officials and most of the community. The lack of Human Resources (HR) in the field of Information Technology (IT) is a very big obstacle to the application of eGovernment in Mamuju District.Teknologi Informasi dan Komunikasi telah menjadi kebutuhan dasar dalam kehidupan masyarakat dan pelayanan oleh pemerintah. Pemerintah selaku pelaksana pelayanan publik menggunakan e-Government sebagai sarana dan prasarana untuk mewujudkan efektif, efisien dan akuntabel. Penerapan e-Government di setiap kabupaten/kota berbeda tingkat efektivitasnya sehingga perlu dilakukan penelitian untuk perbaikan dan penentuan arah kedepan. Penelitian ini dilaksanakan di Kabupaten Mamuju, Provinsi Sulawesi Barat. Pendekatan penelitian ini adalah deskriptif dengan mengunakan jenis penelitian kualitatif yang bertujuan menganalisis hasil pengolahan data berdasarkan indikator teori. Teknik pengumpulan data dilakukan dengan cara wawancara mendalam, observasi, dan studi dokumentasi. Teknik analisis data dengan reduksi data, penyajian data dan pengambilan kesimpulan/verifikasi dengan triangulasi teori, yaitu mendasari teori The Four Forces Model of e-Goverrnent, penelitian di lapangan, dan analisis data untuk mengambil kesimpulan. Hasil penelitian menunjukkan bahwa penerapan e-Government di Kabupaten mamuju belum efektif. Dari dua belas indikator hanya empat  indikator yang terpenuhi. Tidak tercapainya Efektivitas Penerapan e-Government di Kabupaten mamuju disebabkan karena kurangnya pemahaman tentang e-Government pada tingkat eksekutif, pejabat organisasi perangkat daerah, pejabat teknis, dan pejabat legislatif serta sebagian besar masyarakat. Kurangnya Sumber Daya Manusia (SDM) dalam bidang Information Technology (IT) menjadi hambatan yang sangat besar terhadap penerapan e-Governent di Kabupaten Mamuju.